A photoinduced arene–alkyne [3 + 2] cycloaddition cascade of 1-alkynylnaphthalen-2-ols for tunable synthesis of skeletally diverse bridged hexacycles. Issue 9 (1st March 2021) - Zhu, Chi-Fan; Zhang, Jie; Zhu, Yi-Long; Hao, Wen-Juan; Tu, Shu-Jiang; Wang, De-Cai; Jiang, Bo
Abstract : Photoinduced solvent-dependent cyclodimerizations of 1-alkynylnaphthalen-2-ols were developed for the first time, producing skeletally diverse bridged hexacyclic architectures with good yields and high stereoselectivities. Abstract : Photoinduced arene–alkyne [3 + 2] cycloaddition cascades of 1-alkynylnaphthalen-2-ols without a photosensitizer were developed for the first time, enabling tunable synthesis of skeletally diverse bridged hexacyclic architectures with good yields and complete stereoselectivities through solvent-dependent divergent dearomatized cyclodimerizations. The photocatalysis in N, N -dimethylformamide (DMF) delivered functionalized bicyclo[3.2.1]octane-containing bridged oxa-heterocycles, whereas tetrahydrofuran (THF) oriented high stereoselectivity to offer bridged carbocycles. The reaction pathway generates two classes of complex three-dimensional structures that evolve from the same planar internal alkynes.